Strengthening Mahabbah, Mujahadah and Sa’adah through Fitrah-Based Education in Non-Formal Education - Maulidya Nisa; Aceng Kosasih; Nurti Budiyanti (Khazanah Pendidikan Islam, 2025)
This study aims to analyze the concept of fitrah as a foundation in Sekolah Fitrah to strengthen Islamic values such as mahabbah or love, mujahadah or perseverance, and sa'adah or happiness. This study is important because of the urgency related to the general issue of declining motivation in the younger generation. This study uses a qualitative approach with interview and observation methods. Data were collected through direct observation of learning activities and interviews with the principal, curriculum team and teachers. The results of the study indicate that Fitrah-based education emphasizes the learning process that is not only seen as a task but also as a useful experience and produces love, perseverance, and happiness. Researchers focus on emphasizing the innate nature or nature of students and developing student motivation in various dimensions such as spiritual, intellectual, physical and others. This study has implications related to appropriate educational strategies to overcome general problems related to demotivation, in this case the researcher focuses on education in non-formal institutions as an alternative solution to the implementation of learning. Researchers realize that this study focuses on a limited research location, therefore recommendations for further research are to expand the context or location of the study and analyze more deeply, especially from the psychological aspect.